The Influence of Brand Satisfaction on Brand Loyalty Mediated by Brand Love and Moderated by Brand Reputation - Darma Fadhila Benefita; Raditha Dwi Vata Hapsari; Ikhtiara Kaideni Isharina (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Rising competition within Indonesia's local cosmetics sector necessitates that companies comprehend the elements influencing consumer brand loyalty. This research seeks to explore how brand satisfaction and brand love influence brand loyalty, with brand love serving as a mediating factor and brand reputation functioning as a moderating factor. The study employs a quantitative explanatory methodology. Data was gathered from 290 respondents who use local cosmetic products via a questionnaire and analyzed with suitable statistical techniques. The findings show that brand satisfaction and brand love both positively affect brand loyalty, while brand satisfaction also positively impacts brand love. Mediation analysis demonstrates that brand love plays a significant role in mediating the connection between brand satisfaction and brand loyalty. Nonetheless, brand reputation did not significantly influence this relationship. The research indicates that businesses can boost brand loyalty by increasing customer satisfaction and cultivating emotional ties with consumers via product quality, openness, and steady communication tactics.